Interchangeability of medications and biopharmaceutical implication of taking drugs with fluids other than water: ibuprofen case study - Nataša Bubić Pajić; Irma Mureškić; Božana Jevđenić; Anđelka Račić; Biljana Gatarić (Universidade de São Paulo, 2023)
Abstract The aim of this study was to compare the dissolution properties of ibuprofen solid oral dosage forms commercially available in Bosnia and Herzegovina and to estimate the influence of dissolution medium composition on the drug release. Eight products (A-H) were subjected to in vitro dissolution test using experimental conditions described in USP42-NF37. Dissolution properties of one selected product were examined in the presence of alcohol (22.2% v/v) and fruit juice (22.2% v/v). Products marked B-H complied with the pharmacopeial criteria. Dissolution profile of product B was similar with dissolution profiles of products D, E, F and G and similarity was also found between products A-D, C-G, D-G and E-F. Drug release from most of the examined preparations fitted best to the Weibull kinetic model. In the presence of alcohol in the medium, higher amount of ibuprofen was dissolved. Contrary, ibuprofen dissolved in the presence of fruit juice was significantly lower. Differences in the dissolution profiles of investigated preparations suggest that their interchangeability should be additionally considered and demonstrated with in vivo bioequivalence studies. Presence of different substances in the medium can affect dissolution properties of ibuprofen, emphasizing the importance of the patient's compliance.